2017
DOI: 10.1007/s10549-017-4202-z
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour suppressor EP300, a modulator of paclitaxel resistance and stemness, is downregulated in metaplastic breast cancer

Abstract: PurposeWe have previously described a novel pathway controlling drug resistance, epithelial-to-mesenchymal transition (EMT) and stemness in breast cancer cells. Upstream in the pathway, three miRs (miR-106b, miR-93 and miR-25) target EP300, a transcriptional activator of E-cadherin. Upregulation of these miRs leads to the downregulation of EP300 and E-cadherin with initiation of an EMT. However, miRs regulate the expression of many genes, and the contribution to EMT by miR targets other than EP300 cannot be ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 53 publications
7
60
1
Order By: Relevance
“…Some studies showed that these transcriptional coactivators functioned as tumor-suppressors [9-11], whereas some other studies demonstrated that they were essential for the actions of many oncogenes such as AP-1, c-jun and c-fos [12-14]. Whether CBP promotes apoptosis or cell proliferation appears to be context-dependent, and our study showed here that CBP expression was negatively correlated with the overall survival in lung cancer patients.…”
Section: Introductionsupporting
confidence: 47%
“…Some studies showed that these transcriptional coactivators functioned as tumor-suppressors [9-11], whereas some other studies demonstrated that they were essential for the actions of many oncogenes such as AP-1, c-jun and c-fos [12-14]. Whether CBP promotes apoptosis or cell proliferation appears to be context-dependent, and our study showed here that CBP expression was negatively correlated with the overall survival in lung cancer patients.…”
Section: Introductionsupporting
confidence: 47%
“…In addition to some well-known tumor suppressors, mutations in epigenetic modifiers have become attractive targets in recent years. Emerging studies have demonstrated that some epigenetic modifiers can function as tumor suppressors in specific malignancies, such as BCOR in T/B lymphocyte malignancies [101][102][103], MLL2 in melanoma and follicular lymphoma [104,105], MLL3 in acute myeloid leukemia [106], ARID1A in gynecological cancers (mammary, ovarian, and uterine cancers) [107][108][109][110], and EP300 in epithelial cancers (colon, breast, and ovarian carcinomas) [111,112]. Mutations in tumor suppressors including some epigenetic modifiers result in the impaired expression of functional proteins, some of which have been shown to be correlated with a poor NKTCL outcome (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical staining was performed using antibodies against EP300 (HPA003128, Sigma-Aldrich, St. Louis, MO, USA, dilution 1:200) and E-cadherin (Clone 36, #610181, BD Biosciences, San Jose, CA, USA, dilution 1:200). We have previously validated EP300 antibody specificity using a synthetic peptide, as well as described the standard operating procedure for immunohistochemical staining 15 . All sections were visualized with diaminobenzidine and counterstained with hematoxylin.…”
Section: Ihcmentioning
confidence: 99%